(3GdcaGjI hGdCYdGe ajef hdi Gdjef hScfgG aj GdESdGes - (3GdNRQLj , ehab GdOjf CHh GdMSf,J (B812 (3g` s ((3UdGM GHf Ydi s)
(3ChdgG (B:s
(3Gdjef bWQ eHGQce YXje s
(3BNQgG (B:s
(3hUd Ydi GdeNJGQ eGSQi QcGH hegeG SGQ ai GdHMQ QGcHg s
(3fSNI KGfjIs
(3fSNI NGUI edc CMO GdYdeGA ai Gdjefs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B61s
Keywords: (3GdJGQjNs